Manual de control interno para mejorar las actividades operativas en las áreas administrativas, contable, financiera de la distribuidora de productos masivos al por mayor "MARCSOL" ubicado en Cantón Quevedo para el año 2011 - Juca Reyes, Mayra Yalitza (2012)
This research addressed the problematic organizational, administrative, and financial accounting at the firm MARCSOL, a company located in the province of Los Ríos Region Quevedo, is a consumer products company and is chosen for analysis because it did not have an Internal Control Manual, which was complicated organizational system and generated less utilizes and poor customer service. For this reason, the study was based on surveys of customers, suppliers and workers, which served as variables to test the hypothesis initially, then developed and designed an Internal Control Manual pointing to the organizational needs of the company, policies providers aimed at customers and employees, seeking collective benefits and better job focusing organizational producing results. This served as input administrative, accounting and financial support to existing businesses nationally and locally. In addition to this contribution, the practice joins launch of third-level knowledge acquired at university, generating professional expectations and pointing it administrative development, the conclusions derived from work, which could approve the initial hypotheses in the study with the objectives set, were the mainstays in this work, since the development of an Internal Control Manual, administrative task and demand is legal sources study, is that which is justified by the fact that the density of the investigative work. Also demanded a thorough investigation of fieldwork and literature, conducting surveys to obtain finding and final results tabulated numerically finding as the proposed solution Internal Control Manual in administrative accounting and financial MARCSOL.